A Nonlinear Optimization Design Algorithm for Nearly Linear-Phase 2D IIR Digital Filters - Abdussalam Omar; Dale Shpak; Panajotis Agathoklis; Belaid Moa (Signals, 2023)
In this paper, a new optimization method for the design of nearly linear-phase two-dimensional infinite impulse (2D IIR) digital filters with a separable denominator is proposed. A design framework for 2D IIR digital filters is formulated as a nonlinear constrained optimization problem where the group delay deviation in the passband is minimized under prescribed soft magnitude constraints and hard stability requirements. To achieve this goal, sub-level sets of the group delay deviations are utilized to generate a sequence of filters, from which the one with the best performance is selected. The quality of the obtained filter is evaluated using three quality factors, namely, the passband magnitude quality factor <semantics>Qh</semantics> and the group delay deviation quality factor <semantics>Qτ</semantics>, while the third one is a new quality factor <semantics>Qs</semantics> that assesses the performance in the stopband relative to the minimum filter gain in the passband. The proposed framework is implemented using the interior-point (IP) method in a MATLAB environment, and the experimental results show that filters designed using the proposed method have good magnitude response and low group delay deviation. The performance of the resulting filters is compared with the results of other methods.